Innovation: ice cream in the recovery room rules out chylothorax after thoracic lymphadenectomy and affords same-day chest tube removal - Cerfolio, Robert J.; McCormack, Ashley J. (Frontiers in Surgery, 2024)
Objectives Early removal of chest tubes reduces pain and morbidity. This study aimed to remove chest tubes immediately after robotic pulmonary resection with complete thoracic lymphadenectomy by administering ice cream to rule out chylothorax. Methods This quality improvement study utilized prospectively gathered data from one thoracic surgeon. Patients were given 3.6 fl oz of ice cream in the recovery room within 1 h after their operation. Chest tubes were removed within 4 h if there was no chylous drainage and air leak on the digital drainage system. Results From January 2022 to August 2023, 343 patients underwent robotic pulmonary resection with complete thoracic lymphadenectomy. The median time to ingest the ice cream was 1.5 h after skin closure. The incidence of chylothorax was 0.87% (3/343). Two patients were diagnosed with chylothorax after consuming ice cream within 4 h of surgery. One patient, whose chest tube remained in place due to an air leak, had a chylothorax diagnosed on postoperative day 1 (POD1). All three patients were discharged home on POD1 with their chest tubes in place, adhering to a no-fat, medium-chain triglyceride diet. All chylothoraces resolved within 6 days. None of the remaining patients developed chylothorax postoperatively with a minimum follow-up period of 90 days. Conclusions Providing ice cream to patients after pulmonary resection and complete thoracic lymphadenectomy is an effective and reliable technique to rule out chylothorax early in the postoperative period and facilitates early chest tube removal. Further studies are needed to ensure that this simple, inexpensive test is reproducible.